Chemokines Signature and T Cell Dynamics in Leishmaniasis: Molecular Insight and Therapeutic Application - Shreya Upadhyay; Shashi Kumar; Vishal Kumar Singh; Rahul Tiwari; Awnish Kumar; Shyam Sundar; Rajiv Kumar (Expert Reviews in Molecular Medicine)
Leishmaniasis, caused by obligate intracellular Leishmania parasites, poses a significant global health burden. The control of Leishmania infection relies on an effective T cell-dependent immune response; however, various factors impede the host’s ability to mount a successful defence. Alterations in the chemokine profile, responsible for cell trafficking to the infection site, can disrupt optimal immune responses and influence the outcome of pathogenesis by facilitating parasite persistence. This review aims to emphasize the significance of the chemokine system in T cell responses and to summarize the current knowledge on the dysregulation of chemokines and their receptors associated with different subsets of T lymphocytes during Leishmaniasis. A comprehensive understanding of the dynamic nature of the chemokine system during Leishmaniasis is crucial for the development of successful immunotherapeutic approaches.